The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr9040623
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Studies on Emissions from Diesel Engines Running on Alcohol/Diesel Fuel Blends. A Case Study about Noise Emissions

Abstract: The growing demand for fossil fuels, the rise in their price and many environmental concerns strengthen the incessant search for fuel alternatives. Recently, traffic noise has been described as a threat to human health and the environment, being responsible for premature deaths. In this context, the usage of alcohol/diesel fuel blends in diesel engines has gained increasing impact as a substitute fuel for use in internal combustion engines. Moreover, alcohol can be derived from environmentally friendly process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Another important problem of diesel engines is mechanical vibrations and noise emissions [22][23][24]. These problems negatively affect driving comfort and harm people and the environment [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Another important problem of diesel engines is mechanical vibrations and noise emissions [22][23][24]. These problems negatively affect driving comfort and harm people and the environment [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main source of noise is known as diesel engine, especially in vehicles with diesel engines. Studies to reduce diesel engine noise have increased in importance in recent years [4]. On the other hand, the fact that these values are high is also important for the health of the internal combustion engine operating for a long time [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is to blend the fuels with selective oxygenate additives, such as alcohols and ethers, that can reduce soot formation during combustion. A number of studies have shown that oxygenates, such as methanol [10][11][12], ethanol [10,13,14], n-butanol [15,16], n-octanol [17], dimethyl ether [18], polyoxymethylene dimethyl ether (PODE) [19][20][21][22], and diethyl ether [23][24][25], can reduce soot formation in IC engines. The propensity of oxygenated compounds to reduce soot is not only dependent on the oxygen content, but also strongly depends on the molecular structure, as shown by a number of works [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%